2012
DOI: 10.3390/molecules18010097
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Promising in Vitro Antiproliferative Activity of Sulfones of a 5-Nitrothiazole Series

Abstract: The synthesis in water of new sulfone derivatives under microwave irradiation is described. This eco-friendly process leads to the expected products in good yields by reaction of various substituted sulfinates (commercially available or obtained by reduction of the corresponding sulfonyl chlorides) with 4-chloromethyl-2-methyl-5-nitro-1,3-thiazole. In order to evaluate the antiproliferative effect of these compounds, several sulfone derivatives are also dichlorinated on the Cα next to the sulfonyl group. An ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Aryl and diaryl sulfones has attracted much attention in agrochemicals, 1 medicinal chemistry, biological activities and provided (synthesis) numerous potent sulfone derivatives for different therapeutic (remedial) targets, for example, anti-inflammatory, 2,3 antimicrobial, 4,5 antiproliferative, 6,7 anticancer, 8 antimalarial, 9 cysteine protease inhibitors, 10,11 thyroid receptor ntagonist, 12 EPAC2 antagonist, 13 PI3K/Akt/mTOR signaling pathways inhibitors, 14 and γ-secretase inhibitors. 15 Also, aryl sulfones are found in various drugs such as 4,4 -diamino-diphenyl sulfone (dapsone) 16 and aryl pyrrolyl (and aryl indolyl) sulfones.…”
mentioning
confidence: 99%
“…Aryl and diaryl sulfones has attracted much attention in agrochemicals, 1 medicinal chemistry, biological activities and provided (synthesis) numerous potent sulfone derivatives for different therapeutic (remedial) targets, for example, anti-inflammatory, 2,3 antimicrobial, 4,5 antiproliferative, 6,7 anticancer, 8 antimalarial, 9 cysteine protease inhibitors, 10,11 thyroid receptor ntagonist, 12 EPAC2 antagonist, 13 PI3K/Akt/mTOR signaling pathways inhibitors, 14 and γ-secretase inhibitors. 15 Also, aryl sulfones are found in various drugs such as 4,4 -diamino-diphenyl sulfone (dapsone) 16 and aryl pyrrolyl (and aryl indolyl) sulfones.…”
mentioning
confidence: 99%
“…A range of 5-substituted sulfonylurea derivatives discovered by Li et al [10] showed good herbicidal activities against Amaranthus retroflexus and Brassica campestris for pre-emergence treatment. It is worth noting that compounds containing sulfide, sulfoxide, and sulfone structures have been widely used in materials [11,12], medicine [13][14][15], and pesticides [16][17][18][19][20][21][22] in the past few decades (Figure 1). The pre-emergence herbicide pyroxasulfone, discovered by Todoroki et al [23], exhibited excellent herbicidal activity and crop safety, and it is currently used in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the significant impact of sulfone compounds in biological applications, the development of new sulfone-containing compounds remains one of the central challenges of organic chemistry. [1,2] There are many sulfones widely reported in the literature with a broad spectrum of biological activities such as anticancer, [3] antimicrobial, [4] antiinflammatory, [5] antiproliferative, [6,7] antimalarial [8] and anti-HIV activities. [9] Catalytic chemoselective addition of amino alcohols to α,βunsaturated sulfonyl derivatives leads to the regioselective formation of amino and hydroxy adducts, depending on different catalysts and reaction conditions.…”
Section: Introductionmentioning
confidence: 99%